Simulated conservative tracer as a proxy for S-metolachlor concentration predictions compared to POCIS measurements in Arcachon Bay. (August 2018) - Fauvelle, Vincent; Belles, Angel; Budzinski, Hélène; Mazzella, Nicolas; Plus, Martin
Abstract: The work presented here aims at comparing monitoring of S-metolachlor, the major pesticide in use in the Arcachon Bay (South West of France, transitional coastal area), by chemical analysis (monthly passive sampling) and contaminant dissipation modeling from sources (Mars-2D model). The global strategy consisted in i) identifying the major sources of S-metolachlor to the Bay, ii) monitoring these sources for 12 months, and iii) comparing modeled data in the Bay based on measured inputs, to chemical measurements made inside the Bay along with the 12-month source monitoring. Results first showed that the major S-metolachlor surface inputs to the Arcachon Bay are mainly from one single source. Modeled and measured data were in good agreement at 5 sites in the Bay, both in terms of concentration range and seasonal trends. Modeling thus offers a cost-effective solution for monitoring contaminants in transitional waters, overcoming in addition the technical limitations for measuring pg L −1 or lower levels in coastal waters. However, we highlighted that secondary sources may affect accuracy at local level. Graphical abstract: Simulated S-metolachlor concentrations (ng L −1 ) in the Arcachon Bay surface seawater the 02/11/2011.Unlabelled Image Highlights: S-metolachlor concentration was modeled in the Arcachon Bay using MARS-2D. S-metolachlor originated mainly from one single source. Chemical measurements were in agreement with modeled data.